GROUP GUIDANCE SERVICES BASED ON FOLKLORE FOR STUDENTS JUNIOR HIGH SCHOOL - Supriyanto, Agus; Wahyudi, Amien (Sanata Dharma University Yogyakarta, 2018)
Professional guidance and counseling services are based on a comprehensive guidance and counseling program. Professional counselors were able to implement the program of group guidance based assessment prior to program implementation with four competencies, (1) personality, (2) paedagogy, (3) social, and (4) professional.Â This article discusses the effectiveness of group guidance services through folklore. The fundamental goal of folklore as a medium of group guidance services is the history of the past can foster National Character. The research approach uses literature study. The analysis through descriptive analysis. The findings show that process of group guidance services through the opening stage, intermediate, core activities, and termination. Folklore as the primary basis of group guidance services carried out on the core activities. Folklore presented by the counselor as a group leader and discussed by members with leader of the group to develop a National Character. Folklore in the process of group counseling is effective in order to grow a national character that corresponds to the origin of the formation of the Nation.Â DOI: https://doi.org/10.24071/ijiet.2018.020105